Resistance of cabbage cultivars to Xanthomonas campestris pv campestris - Henz, Gilmar P.; de Melo, Paulo E. (Pesquisa Agropecuaria Brasileira, 1994)
Twenty-five cabbage (Brassica oleracea L., var. capitata) cultivars (13 from Japan, 11 from the Netherlands and the Brazilian cv. Master AG-325) were screened for resistance to Xanthomonas campestris pv campestris under greenhouse conditions. The experimental design consisted on 2-plant plots, with six replications in a complete randomized block design. Each genotype was cultivated in a 4-liter pot. Twenty-eight days after sowing, at the 2-5 true leave growth stage, plants were inoculated by placing a drop of 25 ml of inoculum (108 C FU/ml) in a lesion made on the stem just above the axil of the oldest leaf with an entomological pin. Evaluation was based on a disease rating scale (0 = resistant; 5 = highly susceptible) and on the proportion of internal necrosis length (PNC), obtained by the ratio between necrosis and stem length. Cultivars were classified into four clusters of resistance (average euclidean distance and complete linkage method) considering both rating scale and PNC. There was correlation (r = 0.89) between disease scale and PNC. The following cultivars were considered as resistants: Master AG-325, Arixos F1, Maxim F1, Empax F1, YR Rampo, KKCross, Kenzan, YR 265, YR Ranshu, Ranshu Gold, YR Ranzan and YR Ranju.